Influence of dip-coating times towards oxygen separation performance - Norazlianie, Sazali; Mohd Syafiq, Sharip; Haziqatulhanis, Ibrahim; Ahmad Shahir, Jamaludin; Wan Norharyati, Wan Salleh (IOP Publishing, 2020)
Several advantages possessed by carbon membrane such as can be easily processed, high gas separation performance and requires adequate amount of energy compared to the conventional separation process are the reasons it is deemed as the future media of separation. This study utilized PI blends and nanocrystalline cellulose (NCC) to prepare the tubular carbon membrane in order to investigate its fabrication. The effect of dip-coating duration (15, 30, 45, and 60 min) on physicochemical properties O2/N2 separation was determined. Carbonization was done at 800 °C with 3 °C/min rate of heating under argon gas flow (200 mL/min). Tests of pure gas permeation were conducted in order to study the transport mechanism of prepared carbon membrane at ambient temperature and 8 bar of feed pressure. Carbon membrane with O2 permeance of 29.92 ± 1.44 GPU and O2/N2 selectivity of 9.29 ± 2.54 were obtained after 45 min of dip coating.